2010
DOI: 10.2174/1874364101004010060
|View full text |Cite
|
Sign up to set email alerts
|

Carteolol Hydrochloride Suppresses the Generation of Reactive Oxygen Species and Rescues Cell Death After Ultraviolet Irradiation of Cultured Lens Epithelial Cells

Abstract: Introduction: Anti-oxidant activities of adrenergic β-blockers are proposed in various organs. The aim of the present study was to investigate the effect of carteolol hydrochloride, an adrenergic β-blocker, on the production of reactive oxygen species (ROS) and the viable cell number after ultraviolet irradiation of cultured lens epithelial cells (LECs).Materials and Methodology:Cultured LECs were exposed to 0, 10–5, 10–4, and 10–3 M carteolol hydrochloride for 30 min followed by ultraviolet B (UVB) irradiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…H 2 O 2 is widely used as an oxidant for studies in vitro . Previous research showed that H 2 O 2 injury was able to induce cell apoptosis with concentration and time dependence ( Wang and Huang, 2005 ; Kaji et al, 2010 ; Bai et al, 2012 ). In the present experiment, it is confirmed that SCs treated with 400 μM H 2 O 2 exhibits loss of cell viability.…”
Section: Discussionmentioning
confidence: 99%
“…H 2 O 2 is widely used as an oxidant for studies in vitro . Previous research showed that H 2 O 2 injury was able to induce cell apoptosis with concentration and time dependence ( Wang and Huang, 2005 ; Kaji et al, 2010 ; Bai et al, 2012 ). In the present experiment, it is confirmed that SCs treated with 400 μM H 2 O 2 exhibits loss of cell viability.…”
Section: Discussionmentioning
confidence: 99%